A new species of Pimelodella (Siluriformes: Heptapteridae) from the Guiana Shield, Brazil - Slobodian, Veronica; Akama, Alberto; Dutra, Guilherme Moreira (Zootaxa, 2017)
A new species of Pimelodella is described from the Rio Ipitinga, Rio Jari basin, a left bank tributary of the Rio Amazonas in Brazil. The new species is diagnosed from all congeners by having a dark oval mark on the humeral region. It also differs from all congeners by a unique set of characters, including the presence of 47 to 49 total vertebrae, unpigmented areas dorsally and ventrally adjacent to the dark midlateral stripe, and maxillary barbels reaching at least to vertical through caudal fin insertion. Faunal similarities between the southern part of the eastern Guiana Shield and coastal drainages in the Guianas and Suriname are discussed.